Null Effects of Different Amounts of Task Variation in Both Contextual Interference and Differential Learning Paradigms. Issue 4 (August 2021) - Schmidt, Marcus; Kemena, Markus; Jaitner, Thomas
Various motor learning approaches, such as Schema Theory, Contextual Interference or Differential Learning, have proposed that varying the task during skill acquisition prompts superior learning. However, past research has mainly compared task variation in an experimental group to no task variation in a control group. Past research has more rarely compared specific intervention groups and/or addressed how varying amounts of task variation may affect skill learning. Our aim in this study was to compare motor learning of golf putting across four groups of novice golfers randomly assigned to these conditions: (a) a contextual interference group who putted at varied putting distances and had varied repetitive weekly schedule patterns, (b) a differential learning group who putted at multiple putting distances, putting amplitudes, and putting movements and had no repetitions, (c) an identical differential learning as in (b) except that participants also varied the putter, and (d) a control group who experienced no practice variations. Participants were 42 university students randomly divided into the four groups. All groups completed eight training sessions of 36 putts per session over four weeks, a pretest, posttest, two retention tests (one and three weeks after posttest) and transfer tasks (different floor). Average hit ratios and minimal distances to the hole were captured and analyzed by Scheirer-Ray-Hare test and Mann-Whitney post-hoc tests. Results showed improved hit ratios from pre- to post-test for all groups, and a stable retention performance for the variable training groups in contrast to the control group ( p = .003). Transfer performance was low for all variable training groups with a significantly lower control group performance on transfer test 2 ( p = .008). In conclusion, variable training schedules in all experimental groups benefited motor learning relative to controls, and differences in the amount of task variation between groups with variable training schedules did not affect skill acquisition.